Effect of a Classroom-based Intervention on the Social Skills of Students with Learning Difficulties - Emad M. Alghazo; Mahmoud Gharaibeh; Samer Abdel-Hadi (Emerging Science Journal, 2023)
Children with learning difficulties often face challenges in social skills, hindering their ability to adjust and interact within society. The present study was designed to evaluate the effectiveness of a training program designed to enhance the social skills of individuals with disabilities. The quasi-experimental study involved 20 primary school students with learning difficulties exhibiting deficits in social skills in the United Arab Emirates. To evaluate the level of social skills of the sample children, a social skills assessment scale was employed, which was developed by the researchers. The assessment scale consisted of 24 statements that were organized into three dimensions based on previous research and theoretical frameworks. The results of the present study showed that the training program significantly and positively impacted the social skills of these children. There were statistically significant disparities between the mean ranks of the experimental group and the control group's scores on the social skills assessment scale after program completion. In conclusion, the study recommends integrating the developed training and similar programs into the public and private education curricula, including both government and private schools, to improve the social communication abilities of children with learning difficulties. Doi: 10.28991/ESJ-2023-SIED2-011 Full Text: PDF